Optimization of the Promega PowerSeq™ Auto/Y system for efficient integration within a forensic DNA laboratory. (January 2018) - Montano, E.A.; Bush, J.M.; Garver, A.M.; Larijani, M.M.; Wiechman, S.M.; Baker, C.H.; Wilson, M.R.; Guerrieri, R.A.; Benzinger, E.A.; Gehres, D.N.; Dickens, M.L.
Highlights: The Promega PowerSeq™ Auto/Y System Prototype workflow was optimized. Manual processing and the number of steps in the protocol were reduced. All results obtained were concordant with capillary electrophoresis data. Automation of the optimized workflow decreased manual processing time by 12 h. Abstract: The application of massively parallel sequencing (MPS) is growing in the forensic DNA field, as forensic DNA laboratories are continuously seeking methods to gain information from a limited or degraded forensic sample. However, the laborious nature of current MPS methodologies required for successful library preparation and sequencing leave opportunities for improvement to make MPS a practical option for processing forensic casework. In this study, the Promega PowerSeq™ Auto/Y System Prototype, a MPS laboratory workflow that incorporates multiplex amplification, was selected for optimization with the objectives to introduce automation for relieving manual processing, and to reduce the number of steps recommended by the standard protocol. Successful changes in the optimized workflow included a switch from column-based PCR purification to automatable bead-based purification, adoption of the library preparation procedures by a liquid handling robot platform, and removal of various time-consuming quality checks. All data in this study were found to be concordant with capillary electrophoresis (CE) data and previously-generated MPS results from this workflow. Read abundance and allele balance, metrics related to sample interpretation reliability, were not significantly different when compared to samples processed with the manufacturer's protocol. All the modifications implemented resulted in increased laboratory efficiency, reduced the protocol steps associated with risk of contamination and human error events, and decreased manual processing time by approximately 12 h. These findings provide forensic DNA laboratories a more streamlined option when considering implementation of a MPS workflow.